Effectiveness of condoms in preventing sexually transmitted infections - Holmes King K.; Levine Ruth; Weaver Marcia (The World Health Organization, 2004)
In June 2000, the United States National Institutes of Health (NIH) organized a review of the scientific evidence on the effectiveness of condoms in preventing sexually transmitted infections (STIs). The review concluded that condoms were effective in protecting against transmission of HIV to women and men and in reducing the risk of men becoming infected with gonorrhoea. Evidence for the effectiveness of condoms in preventing other STIs was considered to be insufficient. We review the findings of prospective studies published after June 2000 that evaluated the effectiveness of condoms in preventing STIs. We searched Medline for publications in English and included other articles, reports, and abstracts of which we were aware. These prospective studies, published since June 2000, show that condom use is associated with statistically significant protection of men and women against several other types of STIs, including chlamydial infection, gonorrhoea, herpes simplex virus type 2, and syphilis. Condoms may also be associated with protecting women against trichomoniasis. While no published prospective study has found protection against genital human papillomavirus (HPV) infection, two studies reported that condom use was associated with higher rates of regression of cervical intraepithelial neoplasia and clearance of cervical HPV infection in women and with regression of HPV-associated penile lesions in men. Research findings available since the NIH review add considerably to the evidence of the effectiveness of condoms against STIs. Although condoms are not 100% effective, partial protection can substantially reduce the spread of STIs within populations.